2015
DOI: 10.1007/s40615-015-0100-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving Exercise Adherence and Physical Measures in English-Speaking Latina Women

Abstract: Background Epidemiological data have established that lack of physical activity increases risk factors for chronic diseases. Data also suggests that physical activity participation is lowest in minority women, particularly Latinas, and that the nature of the exercise and attitudes toward exercise may influence exercise adherence. The purpose of this study was to determine the effect of hypertrophy training (HT) or power training (PT) used concomitantly with evaluative conditioning (EC) or neutral conditioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that for women, low intensity exercises have greater adherence and enjoyment than more intense activities (Cox et al, 2003; White et al, 2005). Consistent with this, a strength training intervention with English-speaking Latinas have had relatively low retention and adherence (Martin et al, 2015) compared with interventions promoting walking and other moderate aerobic activities in Latinas (Hartman et al, 2017; Marcus et al, 2015; Pekmezi et al, 2009). Further studies should examine factors influencing initiation and adherence to MSA in Latinas who do not regularly participate in PA (e.g., whether MVPA facilitates MSA initiation and adherence or initiation of MSA is independent of MVPA).…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have shown that for women, low intensity exercises have greater adherence and enjoyment than more intense activities (Cox et al, 2003; White et al, 2005). Consistent with this, a strength training intervention with English-speaking Latinas have had relatively low retention and adherence (Martin et al, 2015) compared with interventions promoting walking and other moderate aerobic activities in Latinas (Hartman et al, 2017; Marcus et al, 2015; Pekmezi et al, 2009). Further studies should examine factors influencing initiation and adherence to MSA in Latinas who do not regularly participate in PA (e.g., whether MVPA facilitates MSA initiation and adherence or initiation of MSA is independent of MVPA).…”
Section: Discussionmentioning
confidence: 80%
“…Evaluative conditioning paradigms in humans usually used visual representations of an object or behaviour for the pairing with the unconditioned stimulus [ 37 ]. In connection with exercise, there are only two studies that applied EC to exercise behaviour using visual stimuli for the exercise representation and the unconditioned stimulus [ 41 , 42 ]; however, only the study by Antoniewicz and Brand [ 42 ] observed acute exercise intensity changes after the EC procedure. To our knowledge, our study is the first study that has used the pairing of a physiological parameter during the performance of the behaviour with a primary reinforcer as UCS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EC is known to produce stable effects in various paradigms using visual and appetitive stimuli as unconditional stimuli [ 38 40 ]. In the context of physical activity, only a few studies performed EC using visual stimuli for conditioning [ 41 , 42 ]. However, sweet rewards are often used in animal conditioning paradigms [ 43 45 ] but less in humans [ 39 , 40 , 46 ].…”
Section: Introductionmentioning
confidence: 99%